Public Protection from The Risk of Criminality Based on Artificial Intelligence from a Legal Perspective Modern Crime - Maria Boekan (West Science Law and Human Rights, 2026)
The development of artificial intelligence (AI) has brought about significant changes in the social, economic, and legal order. Despite the various benefits offered, the use of AI also opens up the possibility of new forms of crime that are increasingly complex, automated, transcend national borders, and difficult to identify. AI-based crimes include automated fraud, identity forgery through deepfake technology, adaptive cyberattacks, misuse of personal data, and transnational cybercrime. These phenomena pose serious threats to public security, national resilience, and public trust in digital governance. Therefore, this study examines crime patterns that utilize AI and analyzes modern criminal law responses to these risks, both in the Indonesian context and internationally. This study uses a normative juridical method with a statutory and conceptual approach to examine criminal law norms, the regulation of cybercrime, and international instruments related to the use of artificial intelligence (AI). The results of the study indicate that modern criminal law still essentially places humans and corporations as the primary subjects of criminal responsibility, while AI is viewed as a means or tool that can be exploited in committing crimes. Therefore, to ensure effective public protection from AI-based crimes, adaptive legal reforms, prevention-oriented law enforcement, strengthening corporate criminal liability, and increased international cooperation are needed.